Creation of cornea biograft - Кавеліна, А. С. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
In recent years, the transplantation of cultured stem cells is considered the most promising method that allows influencing the process of human tissue reparation. Ophthalmologists are studying the possibility of introducing the new technology called ex vivo cultivation of epithelial stem cells to clinic. The technology enables to avoid possible complications connected with limbal autograft transplantation. Different researches by means of methods in vitro and in vivo demonstrated that amniotic membrane can be successfully used as a substrate for epithelial stem cells cultivation and their further application in the treatment of severe ocular surface disease. Peculiarities of the tissue structure and functions of amniotic membrane define the number of characters that can attract researchers and clinicians to use limbal and conjunctival epithelial covering in the treatment of corneal disease.